Perl testing : a developer's notebook - Langworth, Ian.; Chromatic (Sebastopol, CA : O'Reilly, 2005)
Is there any sexier topic in software development than software testing? That is, besides game programming, 3D graphics, audio, high-performance clustering, cool websites, et cetera? Okay, so software testing is low on the list. And that's unfortunate, because good software testing can increase your productivity, improve your designs, raise your quality, ease your maintenance burdens, and help to satisfy your customers, coworkers, and managers. Perl has a strong history of automated tests. A very early release of Perl 1.0 included a comprehensive test suite, and it's only improved from th.
Ch. 1. Beginning testing -- Ch. 2. Writing tests -- Ch. 3. Managing tests -- Ch. 4. Distributing your tests (and code) -- Ch. 5. Testing untestable code -- Ch. 6. Testing databases -- Ch. 7. Testing Web sites -- Ch. 8. Unit testing with test : class -- Ch. 9. Testing everything else.
Includes index.
Print version record.
Keywords: Perl (Computer program language); Perl (Langage de programmation); Perl (Computer program language); Perl (Computer program language)